Conformational Locking of the Geometry in Photoluminescent Cyclometalated N^C^N Ni(II) Complexes - Niazi, Maryam; Maisuls, Iván; Mai, Lukas A.; Schäfer, Sascha A.; Oster, Alex; Diaz, Lukas Santiago; Guldi, Dirk M.; Doltsinis, Nikos L.; Strassert, Cristian A.; Klein, Axel (Molecules (Basel, Switzerland), 2025)
In our research aimed at replacing precious transition metals like platinum with abundant base metals such as nickel for efficient triplet emitters, we synthesized and studied Ni(II) complexes [Ni(LNHR)Cl]. These complexes containing the N^C^N cyclometalating dipyridyl-phenide ligand, equipped with pending H-bonding amine groups (NH(C₆H₅) (LNHPh) and NH(C₆H₅CH₂), ClLNHBn). Molecular structures determined from experimental X-ray diffractometry and density functional theory (DFT) calculations in the ground state showed marked deviation of the Cl− coligand (ancillary ligand) from the ideal planar coordination, with τ4 values of 0.35 and 0.33, respectively, along with hydrogen bonding interactions of the ligand NH function with the Cl− coligand. The complexes exhibit long-wavelength absorption bands at approximately 425 nm in solution, with the experimental spectra being accurately reproduced through time-dependent density functional theory (TD-DFT) calculations. Vibrationally structured emission profiles and steady-state photoluminescence quantum yields of 30% for [Ni(LNHPh)Cl] and 40% for [Ni(LNHBn)Cl] (along with dual excited state lifetimes in the ns and in the ms range) were found in frozen 2-methyl-tetrahydrofuran (2MeTHF) glassy matrices at 77 K. Furthermore, within a poly(methyl methacrylate) matrix, the complexes showed emission bands centered at around 550 nm within a temperature range from 6 K to 300 K with lifetimes similar to 77 K. Based on TD-DFT potential scans along the metal–ligand (Ni–N) coordinate, we found that in a rigid environment that restricts the geometry to the Franck-Condon region, either the triplet T5 or the singlet S4 state could contribute to the photoluminescence.